Water Resources and Economics - Water Resources and Economics (Elsevier, 2026)
Water Resources and Economics is an academic journal published by Elsevier BV. The journal publishes majorly in the area(s): Water resources & Environmental science. It has an ISSN identifier of 2212-4284. Over the lifetime, 208 publications have been published receiving 2917 citations. The journal is also known as: Water resources & economics. Topics: Water resources, Environmental science, Water conservation, Water use, Biology
FI 0.62
Q2
Keywords: Earth; Space & Environmental Sciences; Water Resource Management; Gestión de recursos hídricos; Acuerdos transformativos; Transformative agreements; Economía; Ciencia y tecnología del agua; Geografía, planificación y desarrollo